Pendampingan Kewirausahaan Berbasis Inovasi untuk Meningkatkan Kinerja Usaha Mikro di Desa Asinan Kec. Bawen Kabupaten Semarang - Teti Safari; R.A.Marlien; Heri Usodo; Muhammad Syamsul Maarif; Achmad Kholik (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aimed to improve the performance of micro enterprises through innovation-based entrepreneurship assistance in Asinan Village, Ambarawa, Semarang. The main problems faced by the participants included limited innovation capabilities, weak managerial skills, and low utilization of digital technology in marketing activities. The program adopted a participatory approach through training, intensive mentoring, hands-on practice, and business performance evaluation. A total of 25 micro-enterprise owners participated in this activity. The results demonstrated significant improvements in participants’ entrepreneurial knowledge, innovation capabilities, and utilization of digital marketing. Approximately 72% of the participants successfully developed more innovative products, while 65% began utilizing social media platforms as marketing tools. In addition, participants’ businesses experienced an average revenue increase of 20–30% after completing the mentoring process. These findings indicate that innovation-based entrepreneurship assistance is an effective and sustainable strategy for empowering micro enterprises and strengthening the economy of Asinan Village, Ambarawa, Semarang through collaborative and sustainable community development programs.